2020
DOI: 10.1021/acschembio.0c00032
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Resolution Analyses of Isocoumarin Derivatives for Inhibition of Lysyl-tRNA Synthetase

Abstract: Aminoacyl-tRNA synthetases, the essential enzyme family for protein translation, are attractive targets for developing antibacterial, antifungal, and antiparasitic agents and for treating other human diseases. The antimalarial natural product cladosporin was discovered recently as a novel lysyl-tRNA synthetase (LysRS) specific inhibitor. Here, we report a thorough analysis of cladosporin derivatives using chemical synthesis, biophysical, and biochemical experiments. A series of isocoumarin derivatives with onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 32 publications
(90 reference statements)
4
23
0
Order By: Relevance
“…The complex structure of Pf LysRS-ASP3026 was largely consistent with the structure of Pf LysRS complexing with cladosporin and cladosporin analogs ( 22 , 36 , 37 , 41 ). The room-mean-square deviation (RMSD) between Pf LysRs-ASP3026 and Pf LysRs-cladosporin was 0.733 Å for 449 superimposed Cα atoms ( 36 , 41 ) (Figure 5A ).…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…The complex structure of Pf LysRS-ASP3026 was largely consistent with the structure of Pf LysRS complexing with cladosporin and cladosporin analogs ( 22 , 36 , 37 , 41 ). The room-mean-square deviation (RMSD) between Pf LysRs-ASP3026 and Pf LysRs-cladosporin was 0.733 Å for 449 superimposed Cα atoms ( 36 , 41 ) (Figure 5A ).…”
Section: Resultssupporting
confidence: 68%
“…Nonetheless, apparent decreases in the resonance units (RU) for all concentrations of ASP3026 are observed, which might be attributed to the competition between ATP and ASP3026. In addition, adding the cladosporin analog 3-(cyclohexylmethyl)-6,8-dihydroxy-1H-isochromen-1-one, which exhibits higher activity against Pf LysRS ( 25 , 37 ), completely suppressed the resonance ( Supplementary Figure S7C ), confirming that ASP3026 binds to the ATP pocket of Pf LysRS.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Upon screening these libraries, the unsaturation of the isocoumarin core and transformation of the metabolically unstable tetrahydropyran ring to the cyclohexyl ring yielded a selective LysRS inhibitor with improved metabolic stability at the level of hepatic extraction. In line with a previous report by Rusch et al focusing on metabolic weak points of cladosporin, Zhou et al confirmed that the methyl tetrahydropyran moiety of cladosporin could be replaced by a more stable methylcyclohexane while maintaining potency in the ATP hydrolysis assay (compounds 15, 16) [28]. The methyl group in the cyclohexane ring was important for the hydrophobic interaction with Ser344, resulting in increased potency 4-fold compared to that of compound 15.…”
Section: Cladosporinsupporting
confidence: 73%
“…Upon screening these libraries using the Transcreener AMP assay system to assess aminoacylation by LysRS [23], the unsaturation of the isocoumarin core and transformation of the metabolically unstable tetrahydropyran ring to the cyclohexyl ring yielded a selective LysRS inhibitor with improved metabolic stability at the level of hepatic extraction. In line with a previous report by Rusch et al [26] focusing on metabolic weak points of cladosporin, Zhou et al confirmed that the methyl tetrahydropyran moiety of cladosporin could be replaced by a more stable methylcyclohexane, while maintaining potency in the ATP hydrolysis assay (compounds 15 and 16) [28]. The methyl group in the cyclohexane ring was important for the hydrophobic interaction with Ser344, resulting in increased potency of 4-fold compared to that of compound 15.…”
Section: Cladosporinsupporting
confidence: 66%